STUDY OF OVER THE COUNTER SALE OF ANTIMICROBIALS IN PHARMACY OUTLETS IN PUNE, INDIA: A CROSS SECTIONAL STUDY - S.D. SALUNKHE; V.A.PANDIT; J.S.DAWANE; K.D.SARDA; C.S.MORE (International Journal of Pharma and Bio Sciences, 2013)
Inappropriate use of antimicrobials(AMAs) is a worldwide problem, leading to increasing treatment costs,adverse events and emergence of antibiotic resistant organisms.Self medication,over the counter sale of antimicrobials are some reasons of irrational use of AMAs.Restricting antibiotic use, marketing regulations are important strategies to control this problem.Over the counter sale of AMAs is rarely a focus of study in India.Therefore the present study was aimed to determine the percentage of pharmacies who sale antibiotics without prescriptions involving 263 pharmacies in Pune.Simulated Client Methodology: To obtain AMAS investigator posed as suffering from sore throat or acute diarrhoea.Three levels of demand were used to convience the pharmacists to sell antibiotics.Antibiotics were dispensed in 248 pharmacies.Sore throat & diarrhoea resulted antibiotics dispensed in 123(92.48%) & 125(96.15%) cases respectively. Azithromycin 63(51.21%), Norfloxacin 40(32%) were commonly given for sore throat & diarrhoea respectively. Pharmacies dispensed AMAs in correct dose and duration for sore throat in 64.22% & for acute diarrhoea in 10.4% cases.Only 2% pharmacies asked about allergy history & 8% recommonded for physicians advice. Dispensing antimicrobials without prescription is high in Pune. Most AMAS were dispensed in wrong dose and duration. Health education programmes should be directed to pharmacists & general population.